An empirically based steady state friction law and implications for fault stability. Issue 7 (14th April 2016) - Spagnuolo, E.; Nielsen, S.; Violay, M.; Di Toro, G.
Abstract: Empirically based rate‐and‐state friction laws (RSFLs) have been proposed to model the dependence of friction forces with slip and time. The relevance of the RSFL for earthquake mechanics is that few constitutive parameters define critical conditions for fault stability (i.e., critical stiffness and frictional fault behavior). However, the RSFLs were determined from experiments conducted at subseismic slip rates ( V  < 1 cm/s), and their extrapolation to earthquake deformation conditions ( V  > 0.1 m/s) remains questionable on the basis of the experimental evidence of (1) large dynamic weakening and (2) activation of particular fault lubrication processes at seismic slip rates. Here we propose a modified RSFL (MFL) based on the review of a large published and unpublished data set of rock friction experiments performed with different testing machines. The MFL, valid at steady state conditions from subseismic to seismic slip rates (0.1 µm/s <  V  < 3 m/s), describes the initiation of a substantial velocity weakening in the 1–20 cm/s range resulting in a critical stiffness increase that creates a peak of potential instability in that velocity regime. The MFL leads to a new definition of fault frictional stability with implications for slip event styles and relevance for models of seismic rupture nucleation, propagation, and arrest. Key Points: We describe fault evolution over the entire seismic cycle We describe fault stability over a wide range of experimental (and natural) conditions We account for the diversity of slip events observed at laboratory (and natural) scale